2021
DOI: 10.1111/ivb.12331
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic development of the crinoidPoliometra prolixain the Arctic deep sea

Abstract: Poliometra prolixa is a common species of comatulid crinoid in the Arctic deep sea. In this study, we characterize the ontogenetic development through the cystidean and pentacrinoid stages, using specimens from the LTER (Long‐Term Ecological Research) observatory HAUSGARTEN in the Fram Strait, Arctic Ocean. While embryos and early larval stages (e.g., the doliolaria) were not observed, both post‐settlement stages and adults of P. prolixa were observed on the same moored experimental platform at 2,500 m water d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Crinoids and other suspension feeder invertebrates often colonize elevations on the seabed (Meyer 1980;Genin et al 1986;Messing et al 1990;Messing 2004;Meyer et al 2014). At such heights, the ow of current is faster and more laminar, thanks to which these organisms get a feeding advantage (Vogel et al 1996;Meyer-Kaiser et al 2021). We observed this behavior with the rst crinoid attached to the edge of the platform and the next two attached to the carapace of the crab (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Crinoids and other suspension feeder invertebrates often colonize elevations on the seabed (Meyer 1980;Genin et al 1986;Messing et al 1990;Messing 2004;Meyer et al 2014). At such heights, the ow of current is faster and more laminar, thanks to which these organisms get a feeding advantage (Vogel et al 1996;Meyer-Kaiser et al 2021). We observed this behavior with the rst crinoid attached to the edge of the platform and the next two attached to the carapace of the crab (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Generations of echinoderm researchers have referred to ossicle “fusion” in the formation of fixed joints of various groups of echinoderm (Clark & Downey, 1992; Fell, 1963a, 1963b; Fewkes, 1887; Hendler, 1978, 2018; Hotchkiss & Glass, 2012; Hyman, 1955; Irimura & Fujita, 2003; Meyer‐Kaiser et al, 2021; Murakami, 1963; Smith et al, 1995; Stöhr & Martynov, 2016). In much of the literature, it is unclear what the authors meant by “fusion.” It is likely that fusion has been inferred from failure of ossicles to separate upon treatment with bleach (e.g., Mortensen, 1933).…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of this article, it has been revealed that the crinoid specimens do not belong to Bathycrinus carpenterii but rather the comatulid species Poliometra prolixa (Meyer‐Kaiser et al 2021). In addition, the “small round white sponge” in our 2019 paper is an hexactinellid sponge, possibly Caulophacus arcticus , whereas sponges called “small round white sponge” by other authors working in the HAUSGARTEN belong to the demosponge species Tentorium semisuberites (e.g., Bergmann et al 2011, Taylor et al 2017).…”
mentioning
confidence: 99%